Evaluasi Karakteristik Psikometrik Tes Bakat Differensial dengan Teori Klasik - Farida Agus Setiawati; Rita Eka Izzaty; Veny Hidayat (HUMANITAS: Indonesian Psychological Journal, 2018)
The aims of the research were to analyze the psychometric characteristics of a set Differential Aptitude Test (DAT) consisting of five subtests, they are: numerical, abstract reasoning, space relation, and mechanics. This research using quantitative research method. The data ware collected from documentation pschological testing in UNY. The total data of the study are 2118 youth students in Yogyakarta. The analysis of psychometric characteristics of instrument using classical approach. The characteristic instrument are index of difficulty, index of disciminancy, effectifitas distractor, and reliability coefficient. The data were analyzed with Microcat ITEMAN 3.0 program. The result of analysis can be concluded that there are many information about item characteristic. The items characteristik have variation in index difficulty. Majority items have good index discimination, and many items are bad or need improvement. The items of abstract reasoning subtes have most distractor option which are not functioning properly, and all subtests in DAT instruments are reliable.